2007
DOI: 10.1186/1471-2199-8-63
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 TAR element is processed by Dicer to yield a viral micro-RNA involved in chromatin remodeling of the viral LTR

Abstract: Background: RNA interference (RNAi) is a regulatory mechanism conserved in higher eukaryotes. The RNAi pathway generates small interfering RNA (siRNA) or micro RNA (miRNA) from either long double stranded stretches of RNA or RNA hairpins, respectively. The siRNA or miRNA then guides an effector complex to a homologous sequence of mRNA and regulates suppression of gene expression through one of several mechanisms. The suppression of gene expression through these mechanisms serves to regulate endogenous gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
250
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(258 citation statements)
references
References 105 publications
8
250
0
Order By: Relevance
“…Interestingly, several studies have revealed the existence of retroviral HIV-1-encoded miRNAs. Klase et al (37) showed that processing of the HIV-1 TAR element creates a miRNA that contributes to viral latency. Further work is in progress to identify the in vivo target repertoire of the complete BLV miRNA cluster and elucidate its function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have revealed the existence of retroviral HIV-1-encoded miRNAs. Klase et al (37) showed that processing of the HIV-1 TAR element creates a miRNA that contributes to viral latency. Further work is in progress to identify the in vivo target repertoire of the complete BLV miRNA cluster and elucidate its function.…”
Section: Discussionmentioning
confidence: 99%
“…The low amount of TAR and RRE vsiRNAs identified by various groups may prove to be of importance during a relatively short time frame at the beginning of HIV-1 RNA expression. 49,[72][73][74][75] The displacement of endogenous miRNAs into the RISC mediated by TAR or RRE competition may contribute to mechanisms leading to changes in gene expression and associated pathogenicity in patients.…”
Section: Discussionmentioning
confidence: 99%
“…1A). TAR is a regulatory viral RNA element located at the 5′ end of the HIV-1 retroviral genome that plays many roles in viral replication, including transcription elongation (21), translation (22), dimerization (23), packaging (23), and viral latency (24). TAR contains two functionally important motifs that are separated by four Watson-Crick base pairs: a trinucleotide bulge and a hexanucleotide apical loop (25,26) (Fig.…”
mentioning
confidence: 99%